Synergistic associations of ambient air pollution and heat on daily mortality in India - Jeroen de Bont; Ajit Rajiva; Siddhartha Mandal; Massimo Stafoggia; Tirthankar Banerjee; Hem Dholakia; Amit Garg; Vijendra Ingole; Suganthi Jaganathan; Itai Kloog; Bhargav Krishna; Kevin Lane; et al. (Environment International)
Background: Limited studies have evaluated the interaction between ambient air pollution and heat on mortality, especially in regions such as India, where extreme levels of both exposures occur frequently. Accordingly, we aimed to investigate the potential synergistic effects between ambient air pollution and heat on daily mortality in India. Methods: We applied a time-series analysis for ten cities in India between 2008–2019. We assessed city-wide daily particulate matter ≤ 2.5 μm (PM2.5) and temperature levels using two nationwide spatiotemporal models. We estimated city-specific exposure-outcome associations through generalised additive Poisson regression models, and meta-analysed the associations. To evaluate the interaction between PM2.5 and air temperature (modelled at lag 0–1), a product term was incorporated between linear PM2.5 and non-linear air temperature. From this model, we estimated the effect of air pollution for increasing levels of temperature, and vice versa. Findings: Among ∼ 3.6 million deaths, we found that the association of PM2.5 on mortality was particularly stronger beyond the 75th percentile of temperature. When we compared the associations of PM2.5-mortality at the 75th and 99th temperature percentile, we observed an increase from 0.8 % (95 % CI: −0.3 %, 1.9 %) to 4.6 % (95 % CI: 2.9 %, 6.5 %) increase in mortality per 10 μg/m3 increments, respectively. In addition, we observed a 22.0 % (95 % CI: 13.5 %, 31.2 %) increase in daily mortality risk due to an increase in temperature from the 75th to the 99th city-specific percentiles. Percent change in mortality risk increased linearly from 8.3 % (95 % CI: 2.2 %, 14.9 %) when daily PM2.5 was 20 μg/m3 to 63.9 % (95 % CI: 38.7.%, 93.7 %) at 100 μg/m3. Interpretation: Our findings reveal a substantial synergistic interaction between ambient air pollution and temperature in India. This calls for efforts to tangibly reduce common sources of air pollution and climate change to immediately lower their combined effects on daily mortality and mitigate their long-term health consequences.